2000
DOI: 10.1039/a907568b
|View full text |Cite
|
Sign up to set email alerts
|

On-column derivatization of oligodeoxynucleotides with ferrocene

Abstract: The solid-phase synthesis and characteristics of ferrocenoyl propargylamide (FPA)-labeled oligodeoxynucleotides are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…The Sonogashira reaction has been used to react solidbound oligonucleotides containing iodouridine (5-IdU) or bromoadenosine (8-BrdA) with a propargylamine-functionalized ferrocene 4 ( Figure 2). 23,24 Recently, click chemistry has been used to add multiple ferrocene moieties to DNA at both the 5¤-position 5 25 and the backbone, with the latter approach yielding up to five adjacent ferrocenes. 26 A more unusual example of the postsynthetic incorporation of an organometallic moiety into DNA was shown by Jäschke and co-workers, 27 whose DNA dieneiridium(I) system was shown to enantioselectively catalyze allylic amination reactions.…”
mentioning
confidence: 99%
“…The Sonogashira reaction has been used to react solidbound oligonucleotides containing iodouridine (5-IdU) or bromoadenosine (8-BrdA) with a propargylamine-functionalized ferrocene 4 ( Figure 2). 23,24 Recently, click chemistry has been used to add multiple ferrocene moieties to DNA at both the 5¤-position 5 25 and the backbone, with the latter approach yielding up to five adjacent ferrocenes. 26 A more unusual example of the postsynthetic incorporation of an organometallic moiety into DNA was shown by Jäschke and co-workers, 27 whose DNA dieneiridium(I) system was shown to enantioselectively catalyze allylic amination reactions.…”
mentioning
confidence: 99%
“…Previously, the palladium(0)-catalysed Sonogashira reaction was performed on a solid support of ONs possessing 5-iodopyrimidines, [38] 8-bromopurines [39] as well as 2-or 4-iodobenzyl-or 4-ethynylbenzylglycerols. [28,40] No side-reactions were observed for native nucleobases with protecting groups.…”
Section: Resultsmentioning
confidence: 99%
“…[28,40] No side-reactions were observed for native nucleobases with protecting groups. [38] For the post-synthetic Sonogashira reaction using automated DNA synthesis we prepared 5'-DMT-on ONs ON1-ON3 containing a single internal insertion of one of the following functionalised DNA building blocks: 2'-deoxy-5-ethynyluridine (V; Scheme 1), 2'-deoxy-8-bromoguanosine (W) or (R)-1-O-(2-iodobenzyl)glycerol (X; Scheme 4). The phosphoramidites required for oligonucleotide synthesis were either prepared, as in the case of 2'-deoxy-5-ethynyl- [26] and (R)-1-O-(2-iodobenzyl)glycerol, [28] or purchased, as in the case of 8-bromo-2'-deoxyguanosine.…”
Section: Resultsmentioning
confidence: 99%
“…Houlton and coworkers 84 reinvestigated this reaction and it was reported that it is possible to suppress the cyclization by running the Sonogashira reaction at room temperature for 4 h. Houlton and coworkers 85 also made use of trimethylammoniummethylferrocene iodide as a source of the ferrocenemethyl cation to form Fc-nucleobase conjugates. 86,87 A Sonagashira cross-coupling reaction, using Pd(PPh 3 ) 4 and CuI, links Fc propargylamide to a halogenated base, such as 2 0 -deoxy-5-iodouridine or 8-bromo-2 0 -deoxyadenosine, which has been previously incorporated in the ODN strand (see Scheme 10.2). Figure 10.11 shows the structure of 1-ferrocenylmethylcytosine.…”
Section: Fc-labeled Nucleobasesmentioning
confidence: 99%